2019
DOI: 10.1016/j.adolescence.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐lagged model of the link between parental psychological control and adolescent aggression

Abstract: Introduction:The present study investigated the longitudinal relationship between parental psychological control and adolescent aggression in Chinese adolescents. We also explored whether adolescent gender plays a moderating role in this relationship. Methods: A total of 2458 adolescents (mean age = 13.20 ± 0.65 years; 51.3% male) from Beijing, China, participated at three time points during middle school, 1 year apart. Parental psychological control, adolescent aggression, and demographic characteristics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 50 publications
2
32
0
2
Order By: Relevance
“…The total effect model revealed that PPC was associated with cyberbullying among Chinese adolescents, which supported Hypothesis 1. This result supported SDT (Deci & Ryan, 2008), and is also consistent with the results of empirical studies testing relationships between PPC and other externalizing problems (He et al, 2019). The emotionally manipulative and autonomy-inhibiting nature of PPC might provide a potential explanation of why PPC was associated with externalizing problems such as cyberbullying (Yan et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The total effect model revealed that PPC was associated with cyberbullying among Chinese adolescents, which supported Hypothesis 1. This result supported SDT (Deci & Ryan, 2008), and is also consistent with the results of empirical studies testing relationships between PPC and other externalizing problems (He et al, 2019). The emotionally manipulative and autonomy-inhibiting nature of PPC might provide a potential explanation of why PPC was associated with externalizing problems such as cyberbullying (Yan et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have supported this view. For example, PPC has been verified to be associated with aggression (He et al, 2019), a crucial risk factor for cyberbullying (Song et al, 2019). Furthermore, an authoritarian parental style, namely applying punitive and harsh practices, is also closely related to both cyberbullying and cybervictimization (Makri-Botsari & Karagianni, 2014).…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…In PPC, parents invade children's inner world, ignore their emotions, restrict their expression, and control them through withdrawal of love and inducing of guilt to make children's thoughts, behaviors, and emotions consistent with their own requirements (Barber, 2002). Blossom et al (2016) showed that PPC positively predicted adolescents' externalizing problems significantly, such as bullying and aggression and those problems worsened with the increase of PPC (He et al, 2019). Parents who practice psychological control regard their children as an extension of their own development rather than as an independent individual, which makes it difficult for their children to develop a high sense of selfefficacy and identity (Miri & Limor, 2018).…”
Section: "The Double Whammy Effect": Parental Psychological Control A...mentioning
confidence: 99%
“…Over time, the exposure to these pressures and the experience of introjected motivational states will frustrate adolescents’ psychological needs for autonomy, potentiating psychological disruptions and symptoms of psychopathology. Indeed, studies implicate parental psychological control as one of the most consistently problematic parenting behaviors with regard to adolescent adjustment, predicting various externalizing problems, such as aggression, drug use, truancy, and delinquency (He, Yuan, Sun, & Bian, 2019; Pinquart, 2017a), and especially internalizing problems, such as lower levels of self-esteem and greater levels of depression and anxiety (Pinquart, 2017b; Rogers et al, 2019; Soenens, Park, Vansteenkiste, & Mouratidis, 2012)…”
Section: A Self-determination Theory Perspective On Parental Psycholo...mentioning
confidence: 99%